Opciones terapéuticas usadas en la dismenorrea primaria en las adolescentes del colegio Unidad Educativa Bernardo Valdivieso - Cuenca Rodríguez, Andrea del Rocío (2014)
The present investigation, in which a survey was conducted of 164 students of the "EDUCATIONAL UNIT BERNARDO VALDIVIESO" in the city of Loja. Using the Descriptive and Transversal Method and use of survey information is collected. Based on the items outlined in the project, the results are: o 60% of the adolescents' EDUCATIONAL UNIT BERNARDO VALDIVIESO ". Primary dysmenorrhea presents at 3-6 months after menarche. o The most affected age group is between the age of 14-17 years, which corresponds to 67%. o In the 164 adolescents studied predominantly lower abdominal pain, cramping, to this, the main accompanying symptoms, LBP corresponding to 35%, followed by 21% depression. o The most widely used therapeutic option for adolescents are herbal infusion corresponding to 44% and secondly consume 21% ibuprofen. o In our study population, 34% misses class for primary dysmenorrhea and 66% did not lack class. Keywords: Primary Dysmenorrhea, therapeutic options, Menstruation, Teen